2017
DOI: 10.1371/journal.pone.0170748
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Neurotrophic and Angiogenic Regenerative Capability during Tendon Healing in a Rat Model of Type-II Diabetes

Abstract: Metabolic diseases such as diabetes mellitus type-II (DM-II) may increase the risk of suffering painful connective tissue disorders and tendon ruptures. The pathomechanisms, however, by which diabetes adversely affects connective tissue matrix metabolism and regeneration, still need better definition. Our aim was to study the effect of DM-II on expressional changes of neuro- and angiotrophic mediators and receptors in intact and healing Achilles tendon. The right Achilles tendon was transected in 5 male DM-II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Hypovascularity and hypocellularity characteristics of native tendon tissues are crucial issues that hinder the clinical healing of tendon-related diseases or injuries [68, 69]. Accumulating evidence suggests that tendon tissues generally possess more vessels than commonly believed, although they are recognized as a poorly vascularized tissue type [70].…”
Section: Discussionmentioning
confidence: 99%
“…Hypovascularity and hypocellularity characteristics of native tendon tissues are crucial issues that hinder the clinical healing of tendon-related diseases or injuries [68, 69]. Accumulating evidence suggests that tendon tissues generally possess more vessels than commonly believed, although they are recognized as a poorly vascularized tissue type [70].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature advocates that DM exhibits an essential role in tendon metabolism and healing. In fact, diabetes has been shown to cause non-enzymatic cross-linking [31] and disorganization of collagen fibers [32], promote inflammatory cell invasion and delayed angiogenesis [33], disrupt neurotrophic and angiotrophic factors [5] as well as matrix protein synthesis and degradation [9], and lead to poor biomechanical properties [9,34,35]. Thus, different strategies have been placed to enhance rehabilitation of tendon disorders in patients with DM [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, a growing body of evidence has demonstrated the association between DM and tendinopathy [2,3]. Indeed, this painful connective tissue disorder can affect up to 60% of diabetic patients [4] and cause considerable disability, possibly due to compromised regenerative and healing capability [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al hypothesized that impaired healing in DM may be due to abnormal expression of neurotrophic and angiotrophic factors, as neurotrophins play a prominent role in angiogenesis and re‐innervation within connective tissue, which is crucial for regeneration and homeostasis. Indeed, in a study on rats with injured Achilles tendons, the authors observed significantly lower levels of nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF) in rats with induced DM vs healthy controls.…”
Section: Ligament and Tendon Injuries In Patients With Dmmentioning
confidence: 99%